Role of Land Use Dynamic Nature and Their Influence on Soil Physico-Chemical Properties in Various Watersheds in Ethiopia (JOURNAL OF ADVANCES IN AGRICULTURE, 2024)
Land-use changes have remarkable effects on the dynamics of soil properties.  The lowest mean of bulk density, the highest fraction of clay, soil pH, soil organic matter, total nitrogen, available phosphorus, cation exchange capacity, and exchangeable base were recorded in forest land. Also, soil depth data might fluctuate with increasing soil depth. This variation might be due to inappropriate land use management led to disturbance of soil nutrient status, indicating that the soil condition in the cultivated land and plantation forest is getting below the condition of soils under natural forest and grazing lands. Therefore, needs immediate intervention to protect the remnant natural forest and to replenish the degraded soil properties proper land use plans and soil water conservations are important to enhance and sustain soil fertility and agricultural productivity.